Laser- and g-induced optical absorption of indium-doped sodium-borate glass - Kopyshinsky, A.V.; Okhrimenko, B.A.; Zelensky, S.E.; Danilchenko, B.O.; Shakhov, O.P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2002)
The laser- and g-induced absorption spectra of indium-doped sodium-borate glass are investigated experimentally. The spectra are interpreted with the use of a model that includes three types of indium centers.